PENCADANGAN PIUTANG PADA PERUSAHAAN SUB SEKTOR PERBANKAN DI INDONESIA: DAMPAK PENERAPAN PSAK 71 - Amrie Firmansyah; Muhammad Nizar Arifullah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to review PSAK 71 (2017) implementation on the provision of accounts receivable in banking sub-sector companies in Indonesia. This implementation includes the value of reserves for accounts, preparation of the company, and the impact of company capital. This research uses qualitative methods with content analysis. This research's data uses secondary data in the form of data and information on financial statements of banking companies listed in Indonesia. The research sample selection was carried out with the criteria, namely the banking sub-sector companies listed on the Indonesia Stock Exchange based on ownership and total assets in 2019. The number of samples used in this study was six companies. This study concludes that not all companies disclose information on the allowance for accounts receivable using the new accounting standards, namely PSAK 71 (2017). Besides, companies in the banking sub-sector are generally ready to implement PSAK 71 (2017). Furthermore, the implementation of PSAK 71 impacts the decrease in the capital in each company.